Meat quality and sensory attributes of Pectoralis major muscle in spent chicken subjected to different marination methods - Roslan, N. F.; Aghwan, Z. A.; Ab Aziz, Muhamad Faris; Sazili, Awis Qurni (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
The effects of four marination methods (water, papaya leaves juice, papaya leaves powder, and commercial meat tenderizer) on the meat quality and sensory attributes of cooked (moist and/or grill) Pectoralis major muscle of spent chicken were examined. Pectoralis major muscles from 40 spent chickens were assigned to four marination methods: marinating with 100 mL distilled water, Control (T1) (n = 10); marinating with papaya leaves juice (50 g PLP + 100 mL distilled water), T2 (n = 10); marinating with 50 g papaya leaves powder, T3 (n = 10); and marinating with 50 g commercial meat tenderizer, T4 (n = 10). Results of meat quality revealed the lowest drip loss, cooking loss, and shear force values of samples from T3 as compared to the other treatments. Additionally, myofibril fragmentation index of marinated Pectoralis major muscle from T3 was significantly higher than the other treatments. Among the treatments within the moist cooking method, T3 presented significantly higher scores for tenderness and juiciness and significantly lower score for flavour as compared to T1 and T2. In the grill cooking method, the highest scores for tenderness and juiciness were significantly demonstrated by samples of T2 and T3. Furthermore, samples from T2 had significantly higher score for flavour. Results of the present work demonstrated that marinating spent chicken meat with 50 g papaya leaves powder improved its tenderness and water holding capacity. Furthermore, greater improvement in tenderness and juiciness were observed when meat samples marinated with papaya leaves powder (T3) were further subjected to moist cooking method.